Customer Satisfaction towards Online and Offline Shopping: A Case of Kathmandu Valley - Ojha, Surya Prakash (Nepalese Journal of Economics, 2025)
This study examines the customer satisfaction towards online and offline shopping: A case of Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are price, location, customer experience, product quality, and customer service. The primary source of data is used to assess the opinions of respondents regarding price, location, customer experience, product quality, customer service, and customer satisfaction. The study is based on primary data of 133 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of customer satisfaction towards online and offline shopping in Kathmandu Valley. The study showed a positive impact of price on customer satisfaction. It indicates that affordable price leads to increase in the customer satisfaction. Similarly, the study showed a positive impact of location on customer satisfaction. It indicates that convenient location leads to increase in customer satisfaction. Likewise, the study also revealed a positive impact of customer experience on customer satisfaction. It indicates that better customer experience leads to increase in customer satisfaction. Further, the study observed a positive impact of product quality on customer satisfaction. It indicates that higher the product quality, higher would be the customer satisfaction. In addition, the study observed a positive impact of customer service on customer satisfaction. It indicates that better customer service leads to increase in customer satisfaction.